Effect of upper body training on energy cost of pole running in cross-country skiers - Takeda, M. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Upper body aerobic and/or anaerobic capacity has recently gained importance in cross-country ski races (Millet, Boissiere, and Candau, 2003). Aerobic metabolic capacity assessed during running with the aid of poles on a treadmill (whole body work) indicated that sufficient upper body aerobic capacity may produce good efficiency; this is because low upper body capacity Imposes a relatively high burden on arms and legs, resulting in higher lactate levels in the muscles and blood. This study has been conducted to investigate the effects of 6 months of upper body training in conjunction with general aerobic training on aerobic capacity, muscle endurance, and the energy cost of pole running in cross-country skiers.